2014
DOI: 10.1128/jcm.02433-13
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Mycobacterium bovis Peptides and Host Response Proteins as Biomarkers for Unambiguous Detection of Subclinical Infection

Abstract: e Bovine tuberculosis remains one of the most damaging diseases to agriculture, and there is also a concern for human spillover. A critical need exists for rapid, thorough, and inexpensive diagnostic methods capable of detecting and differentiating Mycobacterium bovis infection from other pathogenic and environmental mycobacteria at multiple surveillance levels. In a previous study, Seth et al. (PLoS One 4:e5478, 2009, doi:10.1371/journal.pone.0005478) identified 32 host peptides that specifically increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 25 publications
2
40
1
4
Order By: Relevance
“…We have shown that mycobacterial peptides circulating in the serum accurately predict bTB infected from bTB negative and exposed animals [9]. We have extended our previous study to investigate another mycobacterial related component, LAM, likely present in serum of bTB infected animals, which may be used with additional pathogen signatures to provide a battery test for subclinical bTB.…”
Section: Discussionmentioning
confidence: 89%
“…We have shown that mycobacterial peptides circulating in the serum accurately predict bTB infected from bTB negative and exposed animals [9]. We have extended our previous study to investigate another mycobacterial related component, LAM, likely present in serum of bTB infected animals, which may be used with additional pathogen signatures to provide a battery test for subclinical bTB.…”
Section: Discussionmentioning
confidence: 89%
“…Such responses may be influenced by previous exposure to other mycobacterial agents, as a high level of homology exists among mycobacterial species. 3 The current testing limitations and the significant economic losses that ensue, as well as the risk of transmission among livestock, human and wildlife emphasize the desperate need for rapid and inexpensive diagnostic methods able to detect and distinguish M. bovis infection from other pathogenic and environmental mycobacteria. [1][2][3][4] More specific diagnostic tests, relying on the identification of the pathogen or its antigens, have proven to be challenging.…”
mentioning
confidence: 99%
“…[10][11][12] The success level of culture can be determined by the growth rates, the inability of potential isolates to adapt to in-vitro culture conditions, especially in situations where the number of bacilli are limiting, which could result in false-negative results by culture. 3,5,9 Also, for bTB in cattle, culture of tissues collected post-mortem is often used to confirm infection. Mycobacteraemia occurrence in infected animals by itself is not sufficient to make blood culture a valuable diagnostic test for bTB, as the long period needed for culture would still hinder its use as a screening test.…”
mentioning
confidence: 99%
“…In addition, emerging and reemerging diseases and public health concerns regarding a rise in pulmonary and cutaneous nontuberculous mycobacteria (NTM, [ 19 , 20 ]) and economic impact of mycobacterial infections of livestock [ 15 ], requires the use of established biochemical and proteomics methodologies to extend studies into these understudied and important pathogens.…”
Section: Introductionmentioning
confidence: 99%